Pituitary stalk interruption syndrome broadens the clinical spectrum of the TTC26 ciliopathy. Issue 3 (3rd August 2020) - David, Odeya; Eskin‐Schwartz, Marina; Ling, Galina; Dolgin, Vadim; Kristal, Eyal; Benkowitz, Ela; Osyntsov, Lidia; Gradstein, Libe; Birk, Ohad S.; Loewenthal, Neta; Yerushalmi, Baruch
Abstract: Ciliopathies are a heterogeneous group of disorders, related to abnormal ciliary function. Severe biliary ciliopathy, caused by bi‐allelic mutations in TTC26, has been recently described in the context of a syndrome of polydactyly and severe neonatal cholestasis, with brain, kidney and heart involvement. Pituitary involvement has not been previously reported for patients with this condition. Pituitary stalk interruption syndrome (PSIS) is a congenital anomaly of the pituitary gland, diagnosed by characteristic MRI findings. We now describe four patients with TTC26 ciliopathy due to a homozygous c.695A>G p.Asn232Ser mutation and delineate PSIS as a novel clinical feature of this disorder, highlighting an important role of TTC26 in pituitary development. Abstract :